Averaged large-signal model of a DC-DC isolated forward resonant reset converter for a solar cell battery charger using internet of things: implementation - Suriyotai Supanyapong; Wachiravit Pattarapongsathi; Anusak Bilsalam; Damien Guilbert; Phatiphat Thounthong (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In this study, an analysis and modeling circuit for controlling battery charge solar cells based on data management through internet of things (IoT) is presented. For this proposed, a DC-DC forward resonant reset converter is employed and can be charged at a constant current and constant voltage. Data management of various parameters using IoT technology is provided, via which notifications can be sent to an external application. The proposed converter can give an output voltage of 14.4 VDC for a voltage range including between 9 and 18 VDC, using an isolated transformer and a halfwave rectifier circuit. The main switch of the forward resonant reset converter can operate under a zero-turn-on condition. This approach has the benefit of utilizing a leaking inductance. Llkp and resonant capacitor Cr to reset the remaining flux saturation on the high-frequency transformer. A simulation model prototype was created and tested at a set switching frequency of 50 kHz, 14.4 VDC constant output voltage, and output power of approximately 29 W. An efficiency of 96% at maximum full load can be reached. The proposed analysis techniques and mathematical model were verified via simulation and experimental results, and the obtained results are in agreement with the theoretical analysis.